Factor Analysis on the Quality of Financial Reports - Shufia Zuhroh (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study attempts to investigate, in part and simultaneously, the effects of information technology, organizational commitment, human resource quality, and internal control system on the caliber of financial reports at the Ministry of Religion Training Center in North Sumatra Regency. All of the participants in this study were workers at the Ministry of Religion's Work Unit in the North Sumatra Regency. This kind of study was conducted using cross-sectional data collection methods, organizational units of analysis, and causal research methodology. Primary data was used as the data source, and it was acquired by sending questionnaires to respondents who prepared financial reports and KPAs. In order to test the research hypothesis, the data analysis technique employs multiple linear regression analysis techniques, a statistical method for determining partial and simultaneous effects between two or more variables influences and descriptive statistical analysis with the help of the SPSS program.